2017
DOI: 10.1002/eji.201646595
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles mediate intercellular communication: Transfer of functionally active microRNAs by microvesicles into phagocytes

Abstract: Cell activation and apoptosis lead to the formation of extracellular vesicles (EVs) such as exosomes or microvesicles (MVs). EVs have been shown to modulate immune responses; recently, MVs were described to carry microRNA (miRNA) and a role for MVs in the pathogenesis of autoimmune diseases has been discussed. Here we systematically characterized MVs and exosomes according to their release stimuli. The miRNA content of viable or apoptotic human T lymphocytes and the corresponding MVs was analyzed. miRNA, prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…21,22 In terms of SLE, miR-34a was reported to be one of the most frequently epigenetically dysregulated miRNAs. 12,23 Our data demonstrated that THRIL silence could not alleviate LPSinduced cell damage when miR-34a was knocked down. Together with the findings that THRIL could repress the expression of miR-34a, here, we briefly concluded that THRIL aggravated HK-2 cell injury induced by LPS might occur via downregulation of miR-34a.…”
Section: Discussionmentioning
confidence: 78%
“…21,22 In terms of SLE, miR-34a was reported to be one of the most frequently epigenetically dysregulated miRNAs. 12,23 Our data demonstrated that THRIL silence could not alleviate LPSinduced cell damage when miR-34a was knocked down. Together with the findings that THRIL could repress the expression of miR-34a, here, we briefly concluded that THRIL aggravated HK-2 cell injury induced by LPS might occur via downregulation of miR-34a.…”
Section: Discussionmentioning
confidence: 78%
“…[21][22][23] During the past few years, circulating miRNAs have drawn much attention in autoimmune diseases including rheumatic diseases. [24][25][26] Exosomes are a kind of extracellular vesicles, which can be found in blood, saliva, urine, cerebrospinal fluid, and milk. Exosomes-encapsulated miRNAs have been shown to modulate immune responses and participate in the pathogenesis of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…MPs also contain messenger RNA (mRNA) as well as microRNA molecules with regulatory properties. As both mRNA and microRNA can influence the pattern of gene expression of a cell which takes up a particle, MPs could potentially serve as vectors for information transfer between cells …”
Section: Content Of Nuclear Molecules In Microparticlesmentioning
confidence: 99%
“…As both mRNA and microRNA can influence the pattern of gene expression of a cell which takes up a particle, MPs could potentially serve as vectors for information transfer between cells. 34,35 Among products released from dead cells, HMGB1 (high mobility group box 1) is a nonhistone nuclear protein that serves as a prototypic alarmin. 36 HMGB1 is 215 amino acids long and can display immunological activity once released from either dead and dying cells or cells stimulated by LPS or other TLR agonists.…”
Section: Molecules In Microparticlesmentioning
confidence: 99%